The continual evolution of competition law. (4th March 2019) - Roth, Sir Peter
Abstract: Since 2000, the principles of UK competition law have largely mirrored EU competition law. The EU courts have sometimes attracted criticism in the UK, and that has been an aspect of the Brexit debate. Looking at the history and evolution of EU competition law, this lecture shows how the EU courts have in reality functioned very much like common law courts in developing the antitrust provisions of broadly worded legislation, with world-wide influence. Further, certain particular features of the EU courts make them well placed to do so. Attention is drawn to the need to make competition law effectively applicable in practice by courts and businesses, and of the significance of choice as well as price in considering competition for the benefit of consumers. The lecture then looks ahead to the challenges facing competition law presented by very large companies in the high tech sectors, in particular through aggregation of data and enhanced network effects. Considering the tools of competition law available to address these challenges, it cautions against a fundamental overhaul, arguing that the concept of abuse of dominance has sufficient flexibility to deal with much of the conduct in these sectors that has anti-competitive effects but that the threshold and test for merger control may need reconsideration. Further, the UK statutory process and remedies of a market investigation, which can be confined to a single enterprise, has an important potential role through which UK competition law could make a distinct contribution.